Prebiotic ability of musa balbisiana colla stems on the growth of Pediococcus acidilactici in vitro and probiotic encapsulation - Singapurwa Ni Made Ayu Suardani; Candra I Putu; Semariyani A.A. Made; Nursini Ni Wayan; Kusumaningsih Purwaningtyas; Jiwantara Gusti Ngurah Oka; Djelantik Sang Ayu Made Agung Prasetiawati (BIO Web of Conferences)
Musa balbisiana Colla banana is a plant that has many benefits, one of which is useful as a traditional medicine using its stems. Banana stems have potential as a source of prebiotics because they contain carbohydrates and oligosaccharides which can support the growth of good bacteria in the digestive tract. Probiotic encapsulation was carried out to determine the role of Musa paradisiaca stems as a prebiotic in digestion. The encapsulation process is carried out using chitosan, carrageenan, and maltodextrin. The results showed that the prebiotic banana stem Musa paradisiaca could increase the growth of Lactobacillus sp. significantly at certain concentrations, with the most optimal results at a concentration of 6.89% compared to the control. Based on test results, Musa paradisiaca stem flour contains a fructan percentage of 0.14 ± 0.001%. The presence of fructan compounds makes Musa paradisiaca stem flour function as an effective source of natural prebiotics. The test results showed that the biocapsulation contained 2.7 x 103 cfu/gram of lactic acid bacteria. This shows that the bioencapsulation process of lactic acid bacteria was successful. Encapsulation can protect probiotics from extreme conditions during processing and storage, as well as from acidic pH in the digestive tract.